Cover Feature: Synthesis and Antitumor Evaluation of Novel Hybrids of Phenylsulfonylfuroxan and Estradiol Derivatives (ChemistryOpen 2/2020) - Wan, Qi (ChemistryOpen, 2020)
The Cover Feature shows the novel hybrid of phenylsulfonylfuroxan and estradiol derivative 11b exhibited the best activity with IC(50) values of 3.58‐0.0008 μm against the MDA‐MB‐231, A2780 and Hela cell lines. NO‐releasing capacity and inhibition of ERK/MAPK pathway signaling might explain the potent antineoplastic activity of 11b. Preliminary pharmacological studies showed that 11b induced apoptosis and hardly affected the cell cycle of MDA‐MB‐231 cell line. More information can be found in the Full Paper by Qui Wan et al. on page 176 in Issue 2, 2020 (DOI: https://doi.org/10.1002/open.201900228).[Image: see text]